(3MGTjI Ydi eNJUQ GHf GdMGLHs - (3GdMfaj GdYdhj GdOgdhj, ejQRGLGf (B- (3TeS GdOjf, MHjH Gddg Hf YHO Gddg, J (B994 (3g`s ((3Ydj CcHQ Hf eMeO HGbQs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3Ydi age eQGO ef cdGeg hJhVjM GdebGUO GdeNaj Wj CQbGeg hHjfgG Ydi fhGVY RGdJ ajgG bOeg Ch WZi ajgG bdeg Ch Yej Yf GdMb agegs
(3BNQgG (B:s
... (3cGf ddfXQ aj GdGcJaGA HGdfXQ aj eWdb (B.. (3Cf jchf GdebjO (B.. (3GdbWY GdQGLM HGdfSHI Edi GdbWY GdebjO HGdQhGjI Edi gPG hbY GdNW GdTQjas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\167s
(3cTa GdXfhf (B2\1853s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3CUhd Gdabgs